Opioid-Associated Deaths in South Carolina, 2013-2016: A Retrospective Review. Issue 4 (December 2017) - Butler, Daniel C.; Batalis, Nicholas I.
Introduction: Rising rates of opioid abuse in the United States have generated an overdose epidemic. Particularly in the last few years, many offices across the country have seen a shift from prescription opioid toxicity to heroin, illicitly produced fentanyl, and, more recently, various fentanyl analogs. Methods: A retrospective review was performed to better characterize the incidence of licit opioid, heroin, fentanyl, and fentanyl analog-associated deaths in South Carolina. Three-thousand three-hundred and fifty autopsy records from the Medical University of South Carolina's forensic pathology division were reviewed to identify cases in which oxycodone, hydrocodone, heroin, fentanyl, and/or fentanyl analogs were detected. Results: In 2013, the incidence of both heroin and fentanyl-associated deaths was relatively rare (2.2% and 0.4%, respectively), but increased somewhat steadily throughout the ensuing years. The incidence of fentanyl-associated death increased from 0.4% to 2.4% between 2013 and 2016. A decrease in fentanyl-associated deaths was noted between 2015 and 2016; however, 2016 saw a dramatic increase in fentanyl analogs, likely accounting for this slight dip. Heroin rose from 2.2% to 4.5% between 2013 and 2016. Combined, heroin and fentanyl accounted for 2.6% of autopsy deaths in 2013 and increased to 7.6% in 2016, with more substantial increases in 2014 and 2015. Licit opioid-associated deaths remained relatively stable throughout the study period and, when identified, were almost always polydrug comixtures. Discussion: These data illustrate general increases in illicit opioid-related deaths. In contrast to larger jurisdictions, particularly in the Midwest and Northeast, heroin continues to contribute most significantly to intoxication deaths, although synthetic fentanyl and fentanyl analog-associated deaths increased dramatically beginning in 2014.